CONTRIBUTION TO THE DEVELOPMENT OF TRIGONOMETRY BY IBN IRAQ AND ABU RAYHAN BERUNI - Sadritdinova , Zulfiya; Lutfillaeva , Shodona (MMIT Proceedings, 2023)
The article discusses the history of trigonometry, the contribution of scientists to the development of trigonometry. Showing consideration Beruni in trigonometry, scientific heritage of Beruni in the field of mathematics, a significant contribution to the development of methods of spherical trigonometry Ibn Iraq, his merits in the development of world science. Historians of the world’s largest scientific minds of his time, rightly recognize the study of scientific creativity Abu Rayhan Beruni, it shows that his views were once a solid foundation of scientific education and training, based on the achievements of progressive thought